Information System Strategy Designation In Xyz People's Economic Bank - Indra Mulana; Mohamad Subchan (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2024)
The proliferation of technology-based financial services or financial technology (fintech) is not only a competitive risk for commercial banks, but also people's economic banks (BPR). In this condition, BPR is also required to make improvements. BPR inevitably faces extraordinary challenges with the development of this technology. Before technology developed as rapidly as it is today, many BPRs relied on good relationships and personal approaches in attracting customers. Although these methods are still relevant today, BPRs also have to rely on technology. This situation prompted the creation of a strategic plan at BPR XYZ. This analysis carries out information system strategic planning using the Ward and Peppard method, in which an analysis stage of the internal, external and internal and external IS/IT business environment is carried out. Then, from this analysis, results were obtained in the form of business IS strategy, IT strategy and IS/IT management strategy. This information system strategic planning is expected to provide the planning that is needed and useful for the company to achieve its business goals.